(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2008)
One year after Zoltán Kodály’s death (1967) great economical and changes began in Hungary. Those changes proved necessarily useful for the living standard of Hungarian people and for the political-economical connections of the non-liberalized country. But (what a strange and thankless situation!) they proved really harmful in the officially and world-wide accepted musical education, based on the Kodály Concept. The “good” crisis of the society caused a “bad” crisis in the system of teaching